Application of a Mouse Ligated Peyer’s Patch Intestinal Loop Assay to Evaluate Bacterial Uptake by M cells - Fukuda, Shinji (MyJove Corporation, 2011)
The inside of our gut is inhabited with enormous number of commensal bacteria. The mucosal surface of the gastrointestinal tract is continuously exposed to them and occasionally to pathogens. The gut-associated lymphoid tissue (GALT) play a key role for induction of the mucosal immune response to these microbes(1, 2). To initiate the mucosal immune response, the mucosal antigens must be transported from the gut lumen across the epithelial barrier into organized lymphoid follicles such as Peyer's patches. This antigen transcytosis is mediated by specialized epithelial M cells(3, 4). M cells are atypical epithelial cells that actively phagocytose macromolecules and microbes. Unlike dendritic cells (DCs) and macrophages, which target antigens to lysosomes for degradation, M cells mainly transcytose the internalized antigens. This vigorous macromolecular transcytosis through M cells delivers antigen to the underlying organized lymphoid follicles and is believed to be essential for initiating antigen-specific mucosal immune responses. However, the molecular mechanisms promoting this antigen uptake by M cells are largely unknown. We have previously reported that glycoprotein 2 (Gp2), specifically expressed on the apical plasma membrane of M cells among enterocytes, serves as a transcytotic receptor for a subset of commensal and pathogenic enterobacteria, including Escherichia coli and Salmonella enterica serovar Typhimurium (S. Typhimurium), by recognizing FimH, a component of type I pili on the bacterial outer membrane (5). Here, we present a method for the application of a mouse Peyer's patch intestinal loop assay to evaluate bacterial uptake by M cells. This method is an improved version of the mouse intestinal loop assay previously described (6, 7). The improved points are as follows: 1. Isoflurane was used as an anesthetic agent. 2. Approximately 1 cm ligated intestinal loop including Peyer's patch was set up. 3. Bacteria taken up by M cells were fluorescently labeled by fluorescence labeling reagent or by overexpressing fluorescent protein such as green fluorescent protein (GFP). 4. M cells in the follicle-associated epithelium covering Peyer's patch were detected by whole-mount immunostainig with anti Gp2 antibody. 5. Fluorescent bacterial transcytosis by M cells were observed by confocal microscopic analysis. The mouse Peyer's patch intestinal loop assay could supply the answer what kind of commensal or pathogenic bacteria transcytosed by M cells, and may lead us to understand the molecular mechanism of how to stimulate mucosal immune system through M cells.